3D printed clamps for fixation of spinal segments in biomechanical testing. (26th August 2021) - Cornaz, Frédéric; Burkhard, Marco; Fasser, Marie-Rosa; Spirig, José Miguel; Snedeker, Jess Gerrit; Farshad, Mazda; Widmer, Jonas
Abstract: 3D printed clamps provide multiple advantages compared to potting for the fixation of spinal specimens and in a recent study, superior fixation stability was reported. The aim of this study was to evaluate the fixation efficacy of 3D printed vertebra clamps during routine application and to present and evaluate a novel clamp for sacrum fixation. Further, public access to the template files is provided. 98 human single-level cadaveric specimens were biomechanically tested in flexion–extension (FE), lateral bending (LB), axial rotation (AR), anteroposterior shear (AS), lateral shear (LS) and axial compression-decompression (AC). Loading amplitudes were +/-7.5 Nm for FE, LB and AR, +/- 150 N for AS and LS and + 400/-100 N for AC. The novel sacrum clamp was used in 8 specimens. The median relative motion between clamps and specimens was 0.6° in FE, 0.7° in LB, 0.3° in AR, 0.5 mm in AS, 0.5 mm in LS and 0.1 mm in AC. With sacrum clamps, the median relative motion was 0.3° in FE, 0.1° in LB, 0.08° in AR, 0.8 mm in AS, 0.7 mm in LS and 0.2 mm in AC. The vertebra clamps used during routine testing provided better stability compared to the values in the literature in all six loading directions (p < 0.05). The sacrum clamp showed superior anchoring stability in three loading directions compared to the caudal vertebra clamps (p < 0.05), while inferior stability was measured in AS (p < 0.001). We conclude that 3D printed vertebra clamps and 3D printed sacrum clamps represent reliable methods for specimen fixation during routine biomechanical testing.